INFORMATION ENGINEERING OF EMERGENCY TREATMENT FOR MARINE OIL SPILL ACCIDENTS - Mu, Lin.; Wang, Lizhe; Yan, Jining ([S.l.] : CRC PRESS, 2019)
Oil spills are a serious marine disaster. Oil spill accidents usually occur in shipping, ports and offshore oil development. Although most are emergent events, once an oil spill occurs, it will cause great harm to the marine ecological environment, andbring direct harm to the economic development along the affected coast as well as to human health and public safety. Information Engineering of Emergency Treatment for Marine Oil Spill Accidents analyzes the causes of these accidents, introduces China's emergency response system, discussestechnologies such as remote sensing and monitoring of oil spill on the sea surface and oil fingerprint identification, studies model prediction of marine oil spill behavior and fate and emergency treatment technologies for oil spills on the sea surface, and emphatically introduces the emergency prediction and warning system for oil spills in the Bohai Sea as well as oil spill-sensitive resources and emergency resource management systems. Features: The status quo and causes of marine oil spill pollution, as well as hazards of oil spill on the sea. The emergency response system for marine oil spills. Model-based prediction methods of marine oil spills. A series of used and developing emergency treatments of oil spill on the sea. This book serves as a reference for scientific investigators who want to understand the key technologies for emergency response to marine oil spill accidents, including the current level and future development trend of China in this field.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design; MATHEMATICS / General; Oil spills -- Cleanup; Oil spills -- Cleanup -- China; Oil spills -- Remote sensing